Investigation into mechanisms and kinetics of asphaltene aggregation in toluene/n-hexane mixtures - Bahram Soltani Soulgani (KeAi Communications Co., Ltd., 2019)
Abstract Determining the rate of asphaltene particle growth is one of the main problems in modeling of asphaltene precipitation and deposition. In this paper, the kinetics of asphaltene aggregation under different precipitant concentrations have been studied. The image processing method was performed on the digital photographs that were taken by a microscope as a function of time to determine the asphaltene aggregation growth mechanisms. The results of image processing by MATLAB software revealed that the growth of asphaltene aggregates is strongly a function of time. Different regions could be recognized during asphaltene particle growth including reaction- and diffusion-limited aggregation followed by reaching the maximum asphaltene aggregate size and start of asphaltene settling and the final equilibrium. Modeling has been carried out to predict the growth of asphaltene particle size based on the fractal theory. General equations have been developed for kinetics of asphaltene aggregation for reaction-limited aggregation and diffusion-limited aggregation. The maximum size of asphaltene aggregates and settling time were modeled by using force balance, acting on asphaltene particles. Results of modeling show a good agreement between laboratory measurements and model calculations.